Jianpi Huayu Decoction Attenuates the Immunosuppressive Status of H22 Hepatocellular Carcinoma-Bearing Mice: By Targeting Myeloid-Derived Suppressor Cells - Xie, Yingjie; Zhang, Yuan; Wei, Xiaohan; Zhou, Cheng; Huang, Yajing; Zhu, Xingwang; Chen, Yongxu; Wen, Huihong; Huang, Xuhui; Lin, Juze; Wang, Ziying; Ren, Yan; et al. (Frontiers in Pharmacology, 2020)
Tumor-induced immunosuppressive microenvironment in which myeloid-derived suppressor cells (MDSCs) plays an important role, remains an obstacle for effective oncotherapy currently. Inducing MDSCs into maturation was confirmed as an effective method to reduce the tumor-bearing host's immunosuppression. Traditional Chinese medicines (TCM) possess characteristics of alleviating immunosuppression of cancer patients and low toxicity. Jianpi Huayu Decoction (JHD) was an experienced formula of TCM for oncotherapy based on TCM theory and clinical practice. We previously observed that JHD attenuated the expression of interleukin-10 (IL-10) and transforming growth factor beta (TGF-β) in tumor. IL-10 and TGF-β were found to be cytokines positively related to immunosuppression induced by MDSCs. Here, our study was designed to further investigate the regulation of JHD on the immune system in the H22 liver-cancer mouse model. Mainly, flow cytometry was used to detect the proportion of immune cells, to analyze the apoptosis, differentiation and reactive oxygen species of MDSCs. We found that JHD significantly reduced the destruction of spleen structure, reduced the proportion of regulatory T cells (Treg) and T helper 17 cells (Th17), and increased the proportion of cytotoxic T lymphotes (CTL), Dendritic cells (DC) and CD11b+Gr-1+cells in spleen, but with no significant change of T helper 1 cells (Th1), T helper 2 cells (Th2) and macrophages. In vitro experiments showed that apoptosis of MDSCs was decreased as the time of JHD stimulation increased, which partly explained the increase of CD11b+Gr-1+cells in the spleen. Meanwhile, JHD could promote the differentiation of MDSCs into macrophages and dendritic cells, attenuate expression of ROS in MDSCs and reduce its inhibition on the proliferation of CD4+ T cells, in vitro. Therefore, that the proportion of CD11b+Gr-1+ cells increased in the spleen of tumor-bearing hosts may not be villainy after treatment, when these drugs suppress the immunosuppressive ability of CD11b+Gr-1+ cells and promote it mature to replenish dendritic cell, at the same time. Generally, JHD may be a complementary and alternative drug for attenuating the immunosuppressive status induced by hepatocellular carcinoma, possibly by promoting differentiation and inhibiting the immunosuppressive activity of MDSCs.